1996
DOI: 10.1063/1.471878
|View full text |Cite
|
Sign up to set email alerts
|

Phase asymmetry in thermocapillary motion

Abstract: It is shown that bulk thermodynamic effects, in addition to surface tension effects, can play a crucial role in thermocapillary phenomena ͑e.g., bubble or droplet thermomigration and phase separation in multi-phase systems subjected to an imposed temperature gradient͒ due to asymmetric thermodynamic properties of the underlying coexisting phases. The resultant new phenomena are elucidated in a representative model of diffusive systems with a conserved order parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…5a of Ref. [6]) Good agreement with the R −1 dependence as predicted in Eq. ( 18) is found supporting the validity of the interface equation approach based on local equilibrium.…”
Section: A Diffusive Casesupporting
confidence: 76%
See 3 more Smart Citations
“…5a of Ref. [6]) Good agreement with the R −1 dependence as predicted in Eq. ( 18) is found supporting the validity of the interface equation approach based on local equilibrium.…”
Section: A Diffusive Casesupporting
confidence: 76%
“…In fact the mesoscopic shift in chemical potential alone drives the slab to the hotter side. This phenomenon will be addressed elsewhere [19].…”
Section: Introducing Driving Termsmentioning
confidence: 92%
See 2 more Smart Citations
“…Previously, Tanaka [4] explored the interplay between wetting and phase separation for organic mixtures using the phase field model, and found that hydrodynamics plays an important role in bicontinuous phase separation. Afterwards, Bhagavatula and Jasnow [5] investigated the influence of Marangoni migration on phase separation. In principle, Marangoni migration originates from the melt temperature gradient, which drives the second liquid phase towards the higher temperature region.…”
mentioning
confidence: 99%